Sistem Informasi Pasien Pada Praktek Dokter Gigi Berbasis Android Native dan Web - Santika, Silvia Ayu; Turaina, Rifa; Sthepanne, Ilfa (JOSTECH: Journal of Science and Technology, 2022)
The patient information system is an information system that can assist patients in ordering consultation schedules and can assist officers in inputting consultation history, making reports and others. This information system consists of two parts, namely the frontend and backend. The frontend is made using native android while the web-based backend is made using the Codeigniter framework. The method used to develop the system uses the waterfall method and the tools for designing the system use the Unified Modeling Language (UML). At this time, at the Maryam Dental Care Dental Practice, the patient registration system and consultation history are still using the manual method in a way that is still written on paper so that patient data is scattered and the patient does not know his consultation history, ordering the doctor's schedule for treatment by coming to the place or contact the Admin using What's App Social Media and the patient waits until the queue number is called. With this system, it can make it easier for patients to take queue numbers and admins in making patient payment transaction reports.